(untitled) - Fell-Carlson, Deborah L.; Deborah L. Fell-Carlson (Clifton Park, N.Y., 2008)
This training resource provides materials needed to successfully run an in-service, continuing education course, or other classroom instruction on caregiver safety in the health care environment. Each module is designed to decrease preparation time for the presenter by including learning activities and tips essential to an effective presentation. Modules accompany the text, Working Safely in Health Care: A Practical Guide, and include how to prevent and avoid on the job injuries, falls, disease transmission, workplace violence, and more. The focus of these training modules is on best practices and sound prevention principles and interventions that do not change with the next round of regulatory rulemaking. Training Modules to Accompany Working Safely in Health Care will help instructors prepare any member of the health care team on how to better protect themselves and their patients from injury or illness
Keywords: Medical personnel; Health facilities; Health Personnel